The Role of Self-Efficacy in AI Use in the Development of Digital Financial Services: An Analytical Study in Commercial Banks - Hayder Hussein Jawad (International Journal on Economics, Finance and Sustainable Development, 2026)
The study aimed at assessing the effect of Self-Efficacy in AI Use (SEAI) (Comfort with AI and AI Technological Skills) on the development of Digital Financial Services (DFS) (Withdrawals via ATMs, Payments via POS terminals, and Online Payments), in order to solve the problem: What is the effect of SEAI on the development of DFS by employees of commercial banks? A descriptive analytical approach was employed and the study used a questionnaire, with a sample of employees in commercial banks in Karbala Governorate (12 banks: Iraqi Investment, Baghdad Investment, Al-Mansour Investment, Iraqi Middle East, International Development Investment, Elaf Islamic, Iraqi Commercial, Iraqi Union, Dar Al-Salam, Ghalib, Al-Janoub, and Islamic World). If 100 questionnaires were distributed and 83 were retrieved, with 5 damaged and 78 valid for analysis, and two analysis packages (SPSS & AMOS) were used, the study found that SEAI has a strong correlation with DFS, and bank employees prioritize artificial intelligence and technical skills in this area to improve DFS, so it is recommended that SEAI mechanisms need to be promoted to encourage the transformation towards electronic payment methods to improve the collection of funds and DFS, which activates prepaid cards and digital wallet technologies and requires an assessment of opportunities available for the proper use to facilitate procedures for institutions to directly rely on electronic payments.